2015
DOI: 10.1089/pop.2014.0154
|View full text |Cite
|
Sign up to set email alerts
|

Automated Telephone Self-Management Support for Diabetes in a Low-Income Health Plan: A Health Care Utilization and Cost Analysis

Abstract: The objective was to determine whether automated telephone self-management support (ATSM) for lowincome, linguistically diverse health plan members with diabetes affects health care utilization or cost. A government-sponsored managed care plan for low-income patients implemented a demonstration project between 2009 and 2011 that involved a 6-month ATSM intervention for 362 English-, Spanish-, or Cantonesespeaking members with diabetes from 4 publicly funded clinics. Participants were randomized to immediate in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…Studies that were included were those published since 2014, with data collected from USA (n = 11) [19][20][21][22][23][24][25][26][27][28][29], UK (n = 3) [30][31][32], Hong Kong (n = 1) [33], Denmark (n = 1) [34], Canada (n = 1) [35], Israel (n = 1) [36] and Australia (n = 1) [37]. There were a range of interventions identified that explored reducing unscheduled hospital care in people with diabetes; telemedicine (n = 3) [20,34,37], education (n = 2) [19,30], integrated care pathways (n = 4) [23][24][25]31], enhanced primary care (n = 7) [26-29, 32, 33, 35] and care management teams (n = 3) [21,22,36]. The study design of the papers were heterogenous; 3 before-after studies [25,26,32], 1 randomised controlled trial (RCT) [37], 4 cohort studies [19,22,23,33], 2 quasi experiments [20,24], 1 cross sectional study [36], 1 mixed method study [34], 4…”
Section: Study Characteristics and Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that were included were those published since 2014, with data collected from USA (n = 11) [19][20][21][22][23][24][25][26][27][28][29], UK (n = 3) [30][31][32], Hong Kong (n = 1) [33], Denmark (n = 1) [34], Canada (n = 1) [35], Israel (n = 1) [36] and Australia (n = 1) [37]. There were a range of interventions identified that explored reducing unscheduled hospital care in people with diabetes; telemedicine (n = 3) [20,34,37], education (n = 2) [19,30], integrated care pathways (n = 4) [23][24][25]31], enhanced primary care (n = 7) [26-29, 32, 33, 35] and care management teams (n = 3) [21,22,36]. The study design of the papers were heterogenous; 3 before-after studies [25,26,32], 1 randomised controlled trial (RCT) [37], 4 cohort studies [19,22,23,33], 2 quasi experiments [20,24], 1 cross sectional study [36], 1 mixed method study [34], 4…”
Section: Study Characteristics and Participantsmentioning
confidence: 99%
“…There were a range of interventions identified that explored reducing unscheduled hospital care in people with diabetes; telemedicine (n = 3) [20,34,37], education (n = 2) [19,30], integrated care pathways (n = 4) [23][24][25]31], enhanced primary care (n = 7) [26-29, 32, 33, 35] and care management teams (n = 3) [21,22,36]. The study design of the papers were heterogenous; 3 before-after studies [25,26,32], 1 randomised controlled trial (RCT) [37], 4 cohort studies [19,22,23,33], 2 quasi experiments [20,24], 1 cross sectional study [36], 1 mixed method study [34], 4 [21,27,35]. The sample size of the 19 papers ranged from n = 25 to n = 104,000.…”
Section: Study Characteristics and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Language-concordant care, delivered through patient counselling or health coaching, is a critical predictor of improved self-management outcomes [ 11 13 ] and can address disparities in health outcomes [ 14 , 15 ]. Technology-assisted diabetes self-management and prevention programs, including those that provide patient-centered supports, have expanded significantly in the last decade with a myriad of approaches including: web-based programs [ 16 , 17 ], SMART phone applications or apps [ 18 , 19 ], telephone-based automated call programs, (often referred to as Automated Telephonic Self-Management Support, or ‘ATSM’ or Interactive Voice Response) which blend narratives content with queries that require patients to respond via touch tone with the information going to a central location for review [ 20 24 ]. However, studies have noted that language-concordant intervention delivery is limited [ 25 ] highlighting a gap in using Health IT to reduce disparities in ways to ensure the digital divide is not exacerbated for low-income, limited English proficient populations.…”
Section: Introductionmentioning
confidence: 99%
“…Language-concordant care, delivered through patient counselling or health coaching, is a critical predictor of improved diabetes self-management outcomes [14,15,16]. Technology-assisted diabetes self-management and prevention programs, including those that provide patient-centered supports, have expanded signi cantly in the last decade with a myriad of approaches including: webbased programs [17,18], SMART phone applications or apps [19,20], telephone-based automated call programs, (often referred to as Automated Telephonic Self-Management Support, or 'ATSM' or Interactive Voice Response) which blend narratives content with queries that require patients to respond via touch tone with the information going to a central location for review [21,22,23,24,25]. Each of these program archetypes provides an e cient platform to deliver multi-lingual content, content tailored to local context, and a range of additional modular features.…”
Section: Introductionmentioning
confidence: 99%